Pandangan Islam Mengenai Negara (Ditinjau dari Pandangan Ibnu Khaldun) - Fathoni Fathoni (SCHOLASTICA: Jurnal Pendidikan dan Kebudayaan, 2020)
This study aims to explain Ibn Khaldun's view of the state. the country described according to Ibn Khaldun had a continuity between human society and the power of the state in counteracting the coming threat. although Ibn Khaldun did not clearly define the country but we can see the characteristics of the state described as having a leader, having knowledge and being authoritative to be able to regulate human society within the country. the results in this study that the state requires a law governing group solidarity so that it can be orderly and orderly and a state or power is a necessary instrument and becomes a necessity in a number of human societies. but religion in a country is not an issue that must be discussed because with the development and existing civilization that religion is not a matter that is relevant to the country.